2020
DOI: 10.1371/journal.pone.0235655
|View full text |Cite
|
Sign up to set email alerts
|

Clinical interpretation of variants identified in RNU4ATAC, a non-coding spliceosomal gene

Abstract: Biallelic variants in RNU4ATAC , a non-coding gene transcribed into the minor spliceosome component U4atac snRNA, are responsible for three rare recessive developmental diseases, namely Taybi-Linder/MOPD1, Roifman and Lowry-Wood syndromes. Next-generation sequencing of clinically heterogeneous cohorts (children with either a suspected genetic disorder or a congenital microcephaly) recently identified mutations in this gene, illustrating how profoundly these technologies are modifying gen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 45 publications
0
17
0
Order By: Relevance
“…Some of the resulting domains such as Stem II and 5’ Stem-Loop bind essential splicing proteins. Most TALS patients carry homozygous or compound heterozygous mutations in the 5’ Stem-Loop, while all RFMN patients carry one of their two variants in Stem II, never found mutated in TALS (Benoit-Pilven et al , 2020). The physiopathological links between RNU4ATAC variants and TALS/RFMN/LWS symptoms remain largely unknown.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some of the resulting domains such as Stem II and 5’ Stem-Loop bind essential splicing proteins. Most TALS patients carry homozygous or compound heterozygous mutations in the 5’ Stem-Loop, while all RFMN patients carry one of their two variants in Stem II, never found mutated in TALS (Benoit-Pilven et al , 2020). The physiopathological links between RNU4ATAC variants and TALS/RFMN/LWS symptoms remain largely unknown.…”
Section: Introductionmentioning
confidence: 99%
“…was used as a negative control. For rescue experiments, constructions of human U4atac snRNA of WT or mutated (c.16G> A, c.51G> A and c.55G> A) sequences were previously described(Benoit-Pilven et al, 2020). snRNA molecules were synthesized using a PCR amplicon as template (forward primer containing the T7 promoter (in italics): 5'-TAATACGACTCACTATAGGGAACCATCCTTTTCTTGGGGTTG-3' and the mMESSAGE mMACHINE™ T7 Transcription Kit (ThermoFisher Scientific), followed by a purification using RNA Clean and Concentrator kit (Zymo Research).…”
mentioning
confidence: 99%
“…So far, no cardiac disease has been linked directly to minor intron splicing. Mutations causing loss-of-function of the minor spliceosome are responsible for rare and complex syndromes, mainly affecting growth and the nervous system ( Benoit-Pilven et al, 2020 ; Doggett et al, 2018 ; Merico et al, 2015 ; Verma et al, 2018 ). However, some MOPD1/TALS and Roifman syndrome patients (caused by mutations in RNU4ATAC ) present with cardiac defects, including coarctation of aorta, Tetralogy of Fallot, atrial septal defect, ventricular septal defect and non-compaction of the heart.…”
Section: Discussionmentioning
confidence: 99%
“…Of note, RNU4ATAC is located at 2q14.2, corresponding to the 11 Mb region of homozygosity identified by chromosomal microarray, but was not pursued given the absence of short stature or evidence of a skeletal dysplasia (Figure 2). RNU4ATAC (NR_023343.1) n.55G>A has been reported in multiple affected individuals in the literature in both the compound heterozygous and homozygous state (Benoit‐Pilven et al, 2020; Pierce & Morse, 2012). This variant was rare, seen in 0.007% of ostensibly healthy controls in gnomAD, and occurred at a conserved nucleotide in the 5′ stem loop of the RNA encoding gene (GERP 5.04).…”
Section: Clinical Reportmentioning
confidence: 99%
“…Epilepsy and neuroendocrine dysfunction have also been documented (Pierce & Morse, 2012). Early death, within the first 2 years of life, has been reported in 70% of published cases (Benoit‐Pilven et al, 2020), with several patients reported to show profound clinical decompensation at the time of an intercurrent, febrile illness (Abdel‐Salam et al, 2012, 2013). In two cases, encephalitis was diagnosed (Abdel‐Salam et al, 2012); however, the acute findings on MR imaging were not characterized.…”
Section: Introductionmentioning
confidence: 99%